A harmonização fiscal europeia - Simões, Alexandre Bernardo Macedo Lopes (2015)
With this dissertation we aim to analyze the most relevant aspects of the excise duties harmonized regime, considering Community origins, but having also in attention all legal specifications of its implementation in Portugal. The legal regime of excise duties is presented as an ambitious theme, considering the challenge of different branches of law that influence this subject, such as Tax, Economic and Community laws, the inescapable influence of customs procedures, or regarding environmental objectives. In the European context, the harmonization of excise duties was seen as a condition for the implementation of the internal market, contributing to undo secular tax barriers between Member States and, since so, ensure fair competition and free movement of services and goods. Along with VAT, the excise duties harmonization process could represent a potential European tax system, essential for a full and integrated single market. In this context, it is essential to pay special attention to specific characteristics of excise duties regime, such as ‘duty suspension arrangement’ applicable during the production phase, storage and movement in certain conditions. The growing importance of excise duties, as for revenue or extra-fiscal purposes, recommends new academic studies on this subject, seeking new opportunities and challenges.